Use Of HPE And Hearing Function Disorder Of Ground Handling Workers At Kualanamu Airport - Safrina Ramadhani (Jurnal Kesehatan Masyarakat Andalas, 2017)
Using of hearing protection equipment (HPE) as a preventive measure to prevent the hearing disorder so that it will not be worse. Many ground handling workers of Kualanamu International Airport are not wearing HPE while working at workplaces with niose intensities > 85 dB. This study aims to find out the use of HPE on workers’ hearing disorder. The study used quantitative method with cross sectional design. The population of this study amounted to 128 people. The samples taken in this study amounted to 55 people by using simple random sampling technique. Samples were 20-40 years old and had no history of ear disease. The use of HPE data were gathered with questionnaires and hearing function disorder with Audiometry. Data analyzed by using bivariate analysis with Chi-Square test (α=0.05). The result of the research showed that 21 respondents (38.2%) did not use HPE and and 36 respondents (65.5%) had hearing disorder. The result of bivariate analysis showed that there is a significant correlation between HPE usage with hearing disorder (p=0.001; OR=11.600; 95% CI=3.121-43.120). The conclusion of this study is that hearing protective equipment is a factor affecting hearing disorder, so it is advisable to ground handling workers to always wear earplugs while working in areas with noise above TLV.